Bahasa Inggris - Wibowo, Josua Divino; Setiawan, Cahyadi; Mataburu, Ilham Badaruddin (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2024)
Cianjur Regency has a high potential for landslides, as seen from the region's topographic parameters. This research aims to map landslide-prone areas in Cianjur Regency using the SMORPH (Slope Morphology) model. The results of landslide susceptibility mapping in Cianjur Regency using the SMORPH model show that 81.87% of the area is in the low susceptibility classification, 13.78% is in the medium classification, and 4.35% of the area is in the high susceptibility classification. Based on the Kappa accuracy test, the level of mapping accuracy with the SMORPH model has an overall accuracy value of 0.875, which means that the mapping results are almost in accordance with field conditions. It is hoped that the results of this research can be used as a reference model for more accurate landslide susceptibility mapping as a form of effort to increase landslide disaster capacity. Keywords: Cianjur Regency, landslide, SMORPH model, susceptibility